PEMBUATAN ALAT PELINDUNG DIRI BAGI TENAGA KESEHATAN SEBAGAI UPAYA PENCEGAHAN PENULARAN COVID-19 DI KECAMATAN KURANJI KOTA PADANG - Rika Susanti; Taufik Hidayat; Noverika Windasari; Citra Manela; Fadhilati Sabrina; Maria Nurlita; Rauffi Hayatul Putri; Popy Puspita Sari; Nadira Ismanel Tamura; Utami Yuliandini; Ovella April Rieza; Afifa Humaira; Zhafira Ferin (LPPM Universitas Andalas, 2024)
Coronavirus Disease 2019 (COVID-19) is a novel disease previously unidentified in humans. The COVID-19 pandemic has necessitated that all medical personnel and health workers wear personal protective equipment (PPE) while serving patients. The pandemic has caused a global shortage of PPE, especially in Indonesia, leading to the closure of many health service facilities, including several in the Kuranji District, to prevent COVID-19 transmission. In response, the community service team of the Faculty of Medicine, Andalas University (FK UNAND), initiated a PPE procurement project for health workers. This activity aimed to supply PPE to medical personnel at the First Level Health Facility (FLHF) in Kuranji District, Padang City. The PPE, including masks, face shields, and gowns/hazmats, was produced following a feasibility study to ensure safety for health workers. The procurement involved collaboration between the FK UNAND community service team and Micro, Small, and Medium Enterprises (MSMEs). The team designed models of masks, face shields, and gowns/hazmats that met health safety standards, sourced the necessary materials, and passed these designs and materials to MSMEs for production. Prior to production, a meeting with MSMEs was held to discuss the designs. Eight MSMEs were selected to produce the PPE over approximately one month. A total of 400 masks, 180 face shields, and 20 gowns were produced and distributed to 8 FLHFs in Kuranji sub-district. The handover of PPE was met with an extraordinary response from health workers, as it significantly addressed the PPE shortage and allowed FLHFs in Kuranji District to resume operations and provide medical services to the community.